Perception of assent in biomedical research among medical specialists and trainees in Abakaliki, Nigeria - Onoh RC; Umeora OUJ; Ezeonu PO; Agwu UM; Lawani LO; Ezeonu CT (Dove Medical Press, 2014)
Robinson Chukwudi Onoh,1 Odidika Ugochukwu Joannes Umeora,1 Paul Olisaemeka Ezeonu,1 Uzoma Maryrose Agwu,1 Lucky Osaheni Lawani,1 Chinonyelum Thecla Ezeonu21Department of Obstetrics and Gynecology, 2Department of Pediatrics, Federal Teaching Hospital Abakaliki, Ebonyi State, NigeriaBackground: Assent is the child's affirmative agreement to participate in research. Consent from parents and assent from children are required in research involving children.Objective: To determine the knowledge, perception, and level of practice of assent in children among medical specialists and trainees in research work as well as the level of ethical norms observed during research.Methods: A semistructural questionnaire was designed for a cross-sectional survey of medical specialists and trainees at the Federal Teaching Hospital Abakaliki at their different departments in the months of January and February 2013. The questionnaires were completed and analyzed.Results: A total of 113 questionnaires were distributed, correctly completed, and analyzed. The mean age of the respondents was 36.2±5.9 years, with a range of 25–55 years. The mean duration of practice was 6.3±3.9 years, with a range of 3–20 years. The majority of respondents were trainees (106, 93.8%). There was no significant association between sociodemographic variables of the respondents and the practice of obtaining assent in research involving children (P>0.05). Ethical clearance was obtained by all medical specialists during their research, but none of those whose research involved children got assent from the children. The majority of medical specialists (80%) and trainees (65.1%) support the practice of assent as a mandatory prerequisite in ethical study. Most of the medical specialists (83.3%) and trainees (65.1%) agree that parents could be influenced by other considerations and benefits in enrolling their children in research. Assent after consent in research involving children in African setting was acknowledged as a necessity by 66.7% of medical specialists and 75.2% of trainees.Conclusion: Assent was observed as a necessary ethical issue in research involving children in this study; however, it is often not sought in our setting.Keywords: children, ethics, consent, assent